1990
DOI: 10.1093/clinchem/36.8.1479
|View full text |Cite
|
Sign up to set email alerts
|

Deamidation of glutamine by increased plasma gamma-glutamyltransferase is a source of rapid ammonia formation in blood and plasma specimens

Abstract: Owing to increased enzymatic hydrolysis of glutamine, additional ammonia is formed in blood and plasma specimens with increased gamma-glutamyltransferase activity (gamma-GT, EC 2.3.2.2.). The close correlation between gamma-GT and glutaminase (EC 3.5.1.2) activities (r = 0.97) in plasma, the inhibition with 6-diazo-5-oxo-L-norleucin or borate plus serine, and the activation with maleate clearly show that gamma-GT itself is the glutamine-deamidating enzyme in plasma. Under pathological conditions, increased gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…31,32 It should also be noted here that there are some ammonia-producing and NADH-consuming side-reactions that result in decreasing absorbance at 340 nm independently of FXIIIa activity. [33][34][35][36] The effect of these side-reactions varies from plasma to plasma and corresponds with 2 to 15% of average normal FXIII activity, which is a serious limitation in the assay specificity. 36 Such an overestimation of FXIII activity, which does not usually cause a problem in the normal range, might produce falsely high levels of FXIII in FXIII-deficient patients, thereby giving misleading information on the severity of FXIII deficiency and on the effectiveness of any replacement therapy.…”
Section: Ammonia-release Assaysmentioning
confidence: 99%
“…31,32 It should also be noted here that there are some ammonia-producing and NADH-consuming side-reactions that result in decreasing absorbance at 340 nm independently of FXIIIa activity. [33][34][35][36] The effect of these side-reactions varies from plasma to plasma and corresponds with 2 to 15% of average normal FXIII activity, which is a serious limitation in the assay specificity. 36 Such an overestimation of FXIII activity, which does not usually cause a problem in the normal range, might produce falsely high levels of FXIII in FXIII-deficient patients, thereby giving misleading information on the severity of FXIII deficiency and on the effectiveness of any replacement therapy.…”
Section: Ammonia-release Assaysmentioning
confidence: 99%
“…This applies even more to blood from patients with liver disease because increased ␥-glutamyl transferase activity, a frequent observation in cirrhotic patients, has been associated with increased enzymatic hydrolysis of glutamine leading to artefactual increased ammonia levels. 22 Therefore, it is advised that blood be analyzed within 15 minutes of collection. 18 In the study by Ong et al, 13 however, analysis was performed somewhat later (within 30 min).…”
Section: Commentsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] The sources of the increase in plasma ammonia concentration in vitro reportedly include deamination reactions in erythrocytes and platelets, and the deamidation of plasma glutamine by γglutamyltransferase (γ-GT). 4,6,[8][9][10] While these studies demonstrated the clinical importance of plasma ammonia specimen integrity, many of these studies were performed with blood collection techniques and analytical methods that are no longer in use. In some cases, blood was collected directly into Erlenmeyer flasks, evacuated glass tubes, or via syringe into dipotassium EDTA.…”
Section: Introductionmentioning
confidence: 99%